Universal Method of Compatibility Assessment for Novel Ablation Technologies With Different 3D Navigation Systems - Pannone, Luigi; Eltsov, Ivan; Ramak, Robbert; Cabrita, David; Verherstraeten, Marc; Gauthey, Anaïs; Sorgente, Antonio; Monaco, Cinzia; Overeinder, Ingrid; Bala, Gezim; Almorad, Alexandre; Ströker, Erwin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background New technologies for ablation procedures are often produced by different companies with no cross-compatibility out of the box. This is not a negligible clinical problem since those separately developed devices are often used together. The aim of this study was to develop a bench-testing method to assess compatibility between the DiamondTemp ablation system (DTA) and the Rhythmia electroanatomic mapping system (EAM). Methods Different setups were tested. DTA was connected to the Rhythmia EAM using the following configurations: 3.1. An Ensite EPT GenConnect box (GCB) and Rhythmia Maestro GCB (Maestro GCB, native Rhythmia setup); 3.2. The Medtronic GCB-E and Maestro GCB; 3.3. The Medtronic GCB-E out via the Medtronic GCB-E directly to the Rhythmia at box 1 (pin A61 to A64). Results The DTA location was represented in real-time on the Rhythmia EAM. A proper tracking of the DTA was observed in all setups tested by visual comparison of physical catheter movements and its representation on EAM. In configuration 3.1, a significant shift was observed after the first radio frequency (RF) application; however, further applications caused no further shift. In setup 3.2, no significant shift was observed. The setup 3.3 showed a massive shift in the catheter position before ablation compared to baseline points acquired using the Orion catheter as a reference. Conclusions A universal and reproducible solution for compatibility testing between the various mapping systems and the ablation catheters has been described. DTA has been demonstrated as compatible with Rhythmia EAM with satisfactory results if a specific setup is used.